Leveraging social comparisons: The role of peer assignment policies - Julien Senn; Jan Schmitz; Christian Zehnder (University of Zurich, Department of Economics, 2023)
Using a large-scale real effort experiment, we explore whether and how different peer assignment mechanisms affect worker performance and stress. Letting individuals choose whom to compare to increases productivity to the same extent as a targeted exogenous matching policy designed to maximize motivational spillovers. These effects are significantly larger than those obtained through random assignment and their magnitude is comparable to the impact of monetary incentives that increase pay by about 10 percent. A downside of targeted peer assignment is that, unlike endogenous peer selection, it leads to a large increase in stress. Using a combination of choice data, text analysis and simulations, we show that the key advantage of letting workers choose whom to compare to is that it allows those workers who want to be motivated to compare to a motivating peer while also permitting those for whom social comparisons have little benefits or are too stressful to avoid them. Finally, we provide evidence that social comparisons yield stronger motivational effects than comparable non-social goals.
Keywords: C93; J24; M54; 330; Social comparisons; productivity; stress; incentives; real effort